FORMULASI DAN EVALUASI FISIK SEDIAAN MASKER GEL PEEL OFF EKSTRAK ETANOL RIMPANG KUNYIT PUTIH (Curcuma Zedoaria) VARIASI KONSENTRASI PVA - Putri, Vania Santika; Amelia, Ajeng Rizqi; Ningsih, Reva Vanestia; Isthiningstyas, Valda (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
White turmeric (Curcuma zedoaria) is a plant that contains secondary metabolite compounds such as flavonoids and saponins which are known to have antioxidant activity. Therefore, white turmeric extract has the potential to be used as an active substance in the manufacture of a peel-off gel mask preparation that is practical to use. The purpose of this study was to design and evaluate the physical characteristics of a peel-off gel mask preparation made from Curcuma zedoaria extract with varying concentrations of PVA as a film-forming agent. The extract was obtained through the maceration method using 96% ethanol solvent with a ratio of simplicia and solvent of 1:10. The variations in PVA concentration used were FI (10%), FII (12%), and FIII (14%). The physical results of the preparation showed that the peel-off gel mask preparation was light brown in color, had no aroma, had a gel texture, and showed physical properties that met the requirements with a pH value of FI = 6.28 ± 0.98; FII = 6.19 ± 0.28; FIII=5.76±0.32, spreadability FI=5.30±2.297 cm; FII=5.25±0.005 cm; FIII=5.24±0.065 cm, drying time in the range of 16.53-18.77 minutes and the adhesive power of the three formulas showed a time of more than 1 second. The results of statistical analysis showed that variations in PVA concentration had a significant effect on viscosity, but did not have a significant effect on pH, spreadability, drying time, and adhesive power.